Teenage births and pregnancies in South Africa, 2017 - 2021 – a reflection of a troubled country: Analysis of public sector data - Barron, P; Subedar, H; Letsoko, M; Makua, M; Pillay, Y (South African medical journal, 2022)
Articles on teenage pregnancies have been proliferating in both the popular press and the medical media. We analysed data available in the public sector database, the District Health Information System, from 2017 to 2021. During this time, the number of births to young teenagers aged 10 - 14 years increased by 48.7% (from a baseline of 2 726, which is very high by developed-country standards) and the birth rate per 1 000 girls in this age category increased from 1.1 to 1.5. These increases occurred year on year in most provinces. In adolescent girls aged 15 - 19, the number of births increased by 17.9% (from a baseline of 114 329) and the birth rate per 1 000 girls in this age category increased from 49.6 to 55.6. These increases also occurred year on year in a continuous upward trend as well as in all provinces, but at different rates. Generally, rates were higher in the more rural provinces such as Limpopo, Mpumalanga and Eastern Cape than in more urban provinces such as Gauteng and Western Cape. The increases during the past 2 years were particularly large and may be due to disruption of health and school services with decreased access to these as a result of COVID-19. These metrics pose serious questions to society in general and especially to the health, education and social sectors, as they reflect socioeconomic circumstances (e.g. sexual and gender-based violence, economic security of families, school attendance) as well as inadequate health education, life skills and access to health services.